PENGARUH FUNGISIDA BENLATE DAN MEDIA PENGEPAKAN DALAM KONDISI KELEMBABAN TINGGI TERHADAP VIGOR DAN VIABILITAS BENIH KAKAO SETELAH PENYIMPANAN - Erida Nurahmi (Jurnal Floratek, 2010)
This study was aimed at determining effect of fungicide Benlate and packaging media in high humidity conditions on cocoa seed vigor and viability.  The design used was a factorial completely randomized design (CRD) 3 by 3 with 3 replications. Fungicides consisted of three levels and packaging materials consisted of three levels. The results showed that fungicide Benlate exerted a significant effect on cocoa seed viability. The highest seed viability and vigor were found at a concentration 0.65% of fungicide, while the best packaging media was a perforated plastic polypropylene.  The best combination was obtained between fungicide Benlate of 0.65% and a perforated plastic polypropylene of packaging media.